Cross-cultural confusions amongst diverse colleagues: what teachers' narratives reveal about intergroup communication. Issue 3 (4th May 2019) - Green, Jennifer
ABSTRACT: Teacher-led initiatives built upon relationships, moral purpose, and a commitment to act have the potential to bring about change in twenty-first century schools. In order to implement and sustain change, teachers must collaborate with diverse colleagues and members of the school community. Intergroup communication across cultural and linguistic divides, though not impossible, is challenging as the data from this study shows. The purpose of the qualitative study was to explore factors that influenced teachers' thinking, behavior, and interactions as they designed and implemented a dual language education program for English Language Learners. Narrative inquiry though a heuristic lens allowed for the gathering of stories that illustrate the lived realities of the participants. Teachers' narratives reveal emergent themes regarding cross-cultural confusions amongst colleagues, warranting further study of intergroup communication in schools.